2021
DOI: 10.21203/rs.3.rs-330423/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Influence of Age and Gender on Normalized Foot Arch Height in Childhood and Adolescence: Cross-sectional Study

Abstract: Normalized arch height (NAH), which can be calculated as the instep height (IH) divided by total foot length (TFL), has been used when comparing the foot arch height, instead of navicular height (NH) because of the difficulty to palpate navicular tuberosity when measuring NH. The aim of current study was to investigate to investigate association between foot length and arch height, change in NAH over age, and distribution of foot type according to age in children and adolescent from 8 to 19 years. Foot scannin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…(18) Kyeongbong Lee et al observed substantial increases in various parameters in an elastic band strengthening group, suggesting its potential use as an assistive device to the knee-ankle complex. (19) Research by Ziwei Qiao et al indicates that elastic band resistance training enhances upper and lower limb myodynamia and may improve joint range of motion and ligament flexibility. In the current study, similar findings were observed, with elastic band strengthening contributing to improved ligament flexibility and muscle strength, resulting in enhanced Navicular Drop (ND) FPI and muscle strength.…”
Section: Discussionmentioning
confidence: 99%
“…(18) Kyeongbong Lee et al observed substantial increases in various parameters in an elastic band strengthening group, suggesting its potential use as an assistive device to the knee-ankle complex. (19) Research by Ziwei Qiao et al indicates that elastic band resistance training enhances upper and lower limb myodynamia and may improve joint range of motion and ligament flexibility. In the current study, similar findings were observed, with elastic band strengthening contributing to improved ligament flexibility and muscle strength, resulting in enhanced Navicular Drop (ND) FPI and muscle strength.…”
Section: Discussionmentioning
confidence: 99%